Не мешайте палачу: [роман] / Александра Маринина - Маринина Александра Борисовна (Бестселлер, 1997)
Экземпляры: ф.2 (2021) / Инвентарный номер: 57091 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: М26 / ББК: 84(2Рос=Рус)